Innovation Ecosystem: Research in the brazilian health sector - Nodari, Cristine Hermann; Nunes, Moema; Pellizzoni, Livia (Journal of Sustainable Competitive Intelligence, 2024)
Objective: The research aimed to investigate the health innovation ecosystem (EIS) in Brazil. Methodology/Approach: Qualitative research, with secondary data collection and data analysis through content in light of the theory on innovation ecosystems. Originality/Relevance: Development of theoretical assumptions that guide the discussion of public policies seeking to overcome the challenges, present in financing, scalability, incorporation and adoption of technologies. Key Findings: Promoted by the National Policy for Technological Innovation in Health (PNITS), the health economic-industrial complex (CEIS) plays a fundamental role in the health sector, in structuring characteristics inherent to an ecosystem, as well as the conditions that converge to a higher level of interactions between the actors. Theoretical/Methodological Contributions: The research contributes, theoretically, by elucidating the relationships of value creation in the EIS and its potential for solving social and health problems, through the implementation of cross-cutting public policies that contemplate the diversity of actors.